A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini) - Yasunaga, Tomohide; Duwal, Ram Keshari (Zootaxa, 2016)
A unique phyline plant bug representing a new genus and a new species, Peniculimiris meniscus, is documented on the basis of a pair of specimens collected from Nakhon Ratchasima, central Thailand and Palawan, the Philippines. The new genus Peniculimiris, herein placed in the tribe Hallodapini, is characteristic in having a bundle of brush-like, stiff setae on the scutellum and presence of a ventral spine on the genital segment of each sex. The phylogenetic position of Peniculimiris in the Hallodapini and the function of the spines are discussed.